1999
DOI: 10.1074/jbc.274.50.35840
|View full text |Cite
|
Sign up to set email alerts
|

A Crucial Role of Sterol Regulatory Element-binding Protein-1 in the Regulation of Lipogenic Gene Expression by Polyunsaturated Fatty Acids

Abstract: The liver, the principal lipogenic organ, is responsible for the conversion of excess dietary carbohydrates to triglycerides. A high carbohydrate diet induces the synthesis of several lipogenic and glycolytic enzymes including acetyl-CoA carboxylase (ACC), 1 fatty acid synthase (FAS), stearoyl-CoA desaturase, ATP citrate lyase, malic enzyme, glucose-6-phosphate dehydrogenase, and pyruvate kinase (PK) (1-3). This coordinate induction of enzymes is due to increased mRNA levels, resulting primarily from the accel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
232
4
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 324 publications
(260 citation statements)
references
References 30 publications
23
232
4
1
Order By: Relevance
“…To investigate whether the reduction of triglyceride in liver can be ascribed to the decrease in mature SREBP-1, we examined a transgenic mouse model, which forcibly expresses a mature form of SREBP-1 protein in the liver (TgSREBP1). Consistent with a previous report, 10 dietary PUFA did not decrease the mature SREBP-1 protein or the mRNA levels of lipogenic genes in the liver of TgSREBP1 mice (data not shown). Accordingly, the triglyceride content of EPA-fed mice was almost equal to mice fed the control diet (Fig.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…To investigate whether the reduction of triglyceride in liver can be ascribed to the decrease in mature SREBP-1, we examined a transgenic mouse model, which forcibly expresses a mature form of SREBP-1 protein in the liver (TgSREBP1). Consistent with a previous report, 10 dietary PUFA did not decrease the mature SREBP-1 protein or the mRNA levels of lipogenic genes in the liver of TgSREBP1 mice (data not shown). Accordingly, the triglyceride content of EPA-fed mice was almost equal to mice fed the control diet (Fig.…”
Section: Resultssupporting
confidence: 93%
“…Based on our previous findings that PUFAs suppress SREBP-1 10 and that SREBP-1-null ob/ob mice have less triglycerides in liver, 5 we hypothesized that PUFA would decrease hepatic triglyceride storage through the reduction of SREBP-1. Our results provide a strong clinical implication that PUFAs are potentially useful for the treatment of hepatic steatosis.…”
Section: Discussionmentioning
confidence: 99%
“…This idea is supported by the fact that the overexpression of mature SREBP1 overrides the PUFA suppression of lipogenic gene expression (Yahagi et al 1999), and by a study using animal models which showed that the decrease of the mature form of SREBP1 after administration of fish oil rich in n-3 PUFA results in decreased expression of lipogenic enzymes including SCD1 (Xu et al 1999). Moreover, n-3 PUFA has been related to the control of the proteolytic processing of SREBP precursors (Pegorier et al 2004) and its modulator effect in decreasing the lipogenesis process through inhibition of SREBP1 in adipocytes (Madsen et al 2005).…”
Section: Discussionmentioning
confidence: 97%
“…Bing et al (1996) pointed out that lipo genic gene transcription is inhibited by polyunsatu rated fatty acids and illustrated that the suppression of hepatic lipogenesis is due, at least in part, to the inhibition of transcription of several genes encod ing proteins involved in both lipogenesis and gly colysis, including fatty acid synthase, stearoyl-CoA desaturase, L-type pyruvate kinase, and the S14 protein. Yahagi et al (1999) also demonstrated that ACC expression in mice may be downregulated by dietary PUFAs. At the same time, ACC mRNA ex pression in the liver of meat rabbits was depressed by dietary ALA. Chatelain et al (1996) reported that the rapid increase in the hepatic CPT 1 mRNA level that ac companies the foetal to neonatal transition in the rat is triggered by the reciprocal change in circu lating insulin and long-chain fatty acid concentra tions.…”
Section: Dressing-out Percentage and Meat Qualitymentioning
confidence: 90%